Enhanced phenomenological models of ion channeling contribution to doping profiles in crystals - Bratchenko, M.I.; Dyuldya, S.V.; Bakai, A.S. (Condensed Matter Physics, 2009)
New phenomenological models are proposed to describe the effect of an ordered lattice structure of crystalline
targets on the as-implanted doping profiles of low-energy heavy ions. The models account for the channeling
kinetics and clarify the effect of bi-directional transitions of ions between random-like and channeled modes
of motion on the target depth dependencies of dopant concentration. They also incorporate a simple model
of the target radiation damaging effect on doping profiles. The presented results of model validation against
the experimental and Monte Carlo computer simulation data and the comparative analysis of the capabilities
of the proposed and the existing models show that the application of a more physically grounded approach
allows us to improve the quality of doping profile description. The theoretical models developed are useful for
obtaining physical parameters of low-energy ion channeling kinetics from the experimental data. Запропоновано новi феноменологiчнi моделi опису впливу впорядкованої структури кристалiчної ґратки мiшеней на профiлi iмплантацiї низькоенергетичних важких iонiв. Моделi враховують кiнетику каналювання та проясняють вплив двобiчних переходiв iонiв мiж хаотичним та канальованим режимами руху на залежностi концентрацiї домiшки вiд глибини занурення у мiшень. Вони також мiстять в собi просту модель впливу радiацiйного пошкодження мiшенi на профiлi занурення. Представленi результати верифiкацiї моделей на експериментальних даних та даних комп’ютерного моделювання методом Монте-Карло поруч iз порiвняльним аналiзом можливостей запропонованих та iснуючих моделей показали, що застосування бiльш фiзично обґрунтованого пiдходу дозволяє покращити опис профiлiв iмплантацiї. Використовуючи запропонованi теоретичнi моделi, можна одержати з аналiзу експериментальних даних фiзичнi параметри кiнетики каналювання iонiв низьких енергiй.